PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI - Saut Purba (Universitas Negeri Jakarta, 2011)
The objective of this research is to study the organizational culture, leadership style, and job satisfaction influence on the deans organizational commitment by private university in North Sumatera province. In this research, 90 samples were selected simple random sampling and data has been analysis by path analysis. The research findings are: (1)organizational culture has a direct effect on job satisfaction, (2) leadership style,has a direct effect on job satisfaction, (3) job satisfaction has a direct effect on organizational commitment, (4) organizational culture has a direct effect on organizational commitment, and (5) leadership style has a direct effect on organizational commitment. Efforts to improve organizational commitment can be done by creating conducive conditions in the workplace, employer-oriented leadership style to the task and the empowerment of subordinates, as well as increase job satisfaction by providing recognition, rewards and incentives, the results of this study can be considered for the next research .